Trading volume and location of trade: Evidence from Jardine group listings in Hong Kong and Singapore - Lau, Sie Ting; McInish, Thomas H (Journal of Banking & Finance, 2003)
The switch in primary exchange listing of members of the Jardine Group from Hong Kong to Singapore provides a unique setting in which to examine changes in exchange listings. Previous studies of listing switches from Nasdaq to AMEX/NYSE find increases in liquidity and positive abnormal returns. Clyde et al. (Journal of Finance 52 (1997) 2103) report decreased liquidity and positive abnormal returns associated with switches from AMEX to Nasdaq. In contrast, we find decreased liquidity as measured by trading volume accompanied by negative abnormal returns––demonstrating that expected liquidity increases are not the sole reason for exchange switches and that management may perceive benefits from a switch in listing even if investors do not. Moreover, evidence is accumulating that the increased liquidity observed by previous researches is only associated with switches from smaller to larger markets. In spite of the fact that trading volume declines after the switch, there are still a sufficient number of Hong Kong investors trading in Singapore to cause a statistically significant decline in trading volume in Singapore when there is a holiday in Hong Kong. Hence, order flow is segmented, but not completely. We find that individual firm trading volume is most closely associated with the market on which it is traded most.